Remarks on the type material and the identity of the name Trifolium multistriatum W.D.J.Koch (T. vesiculosum aggr., Fabaceae) - Scoppola, Anna; Lattanzi, Edda (Phytotaxa, 2016)
Trifolium multistriatum (T. sect. Vesicastrum subsect. Mystillus) is a neglected species currently considered as a synonym of T. setiferum or T. rumelicum. The identity of T. multistriatum compared to the species closely related is briefly discussed and its distinct autonomy is highlighted based on the analysis of relevant literature and herbarium specimens, including the type material. The holotype is indicated here for its name based on an exsiccatum belonging to the gathering cited in the protologue, which is preserved at L. Other relevant related material is preserved at PAD and TSM. The distribution area of T. multistriatum includes Western Balkan Peninsula and Italy. The studied material was mostly collected long time ago. For Southern Italian territory, the most recent records date back to the mid 1900s.